Fat-free mass bioelectrical impedance analysis predictive equation for athletes using a 4-compartment model - Matias, C. N.; Campa, F.; Santos, D. A.; Lukaski, H.; Sardinha, L. B.; Silva, A. M. (International Journal of Sports Medicine, 2021)
Bioelectrical impedance analysis equations for fat-free mass prediction in healthy populations exist, nevertheless none accounts for the inter-athlete differences of the chemical composition of the fat-free mass. We aimed to develop a bioimpedance-based model for fat-free mass prediction based on the four-compartment model in a sample of national level athletes; and to cross-validate the new models in a separate cohort of athletes using a 4-compartment model as a criterion. There were 142 highly trained athletes (22.9±5.0 years) evaluated during their respective competitive seasons. Athletes were randomly split into development (n=95) and validation groups (n=47). The criterion method for fat-free mass was the 4-compartment model. Resistance and reactance were obtained with a phase-sensitive 50 kHz bioimpedance device. Athletic impedance-based models were developed (fat-free mass=- 2.261+0.327*Stature2/Resistance+0.525*Weight+5.462*Sex, where stature is in cm, Resistance is in O, Weight is in kg, and sex is 0 if female or 1 if male). Cross validation revealed R2 of 0.94, limits of agreement around 10% variability and no trend, as well as a high concordance correlation coefficient. The new equation can be considered valid thus affording practical means to quantify fat-free mass in elite adult athletes.